The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.32528/tarlim.v3i2.3946
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Etos Kerja Terhadap Kinerja Guru dan Dampaknya Terhadap Prestasi Belajar Siswa di SMP Muhammadiyah 1 Jember

Abstract: Education which constitutes a conscious effort and is mandated by a constitution not only aims at developing intellectual but also spiritual aspects of individual students. Educational processes thus need to be built upon the work ethic so as to maximize teacher’s performance and to foster students’ learning outcomes. With this mind, the current study was conducted to examine whether the work ethic affected teacher’s performance and students’ achievement. This study employed a quantitative methodology and was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…The study's conclusions demonstrate that performance is positively impacted by work ethic. The results of this study concur with those of studies by Batubara (2021), Bakir (2020), and Adsan (2022), which indicated a strong positive direct relationship between work ethic and teacher performance. The research's findings are consistent with the notion of individual behavior.…”
Section: Discussionsupporting
confidence: 91%
“…The study's conclusions demonstrate that performance is positively impacted by work ethic. The results of this study concur with those of studies by Batubara (2021), Bakir (2020), and Adsan (2022), which indicated a strong positive direct relationship between work ethic and teacher performance. The research's findings are consistent with the notion of individual behavior.…”
Section: Discussionsupporting
confidence: 91%
“…The responsiveness aspect in Tjiptono, 2012). The condition of student satisfaction in the explanation above cannot be separated from the role of teachers' motivation and discipline as the dimension of work ethic affecting the students learning outcomes (Bakir & Setiawan, 2021;Nashir, 2017;Srinawati & Achmad, 2020). Student satisfaction on the tangibles aspects which is related to learning methods or strategies, and learning outcomes notes which are carried out by teachers in the implementation of online learning also have a high level of satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Baigaiimainai he has a passion and a high work ethic so that he can make a positive impact on the environment". In addition, Bakir (2020) found that work ethic has a positive and significant effect on teacher performance with a T-value of 2.26 or 0.46. Tatang (2020: 17), that the work ethic has a positive and significant effect on the performance of teachers at SMK Kecaimaitain Maijai.…”
Section: Research and Information Collectingmentioning
confidence: 98%